Expression and Function of GABA Receptors in Myelinating Cells - Serrano-Regal, Mari Paz; Bayón-Cordero, Laura; Ordaz, Rainald Pablo; Garay, Edith; Limon, Agenor; Arellano, Rogelio O.; Matute, Carlos; Sánchez-Gómez, María Victoria (Frontiers in Cellular Neuroscience, 2020)
Myelin facilitates fast transmission of nerve impulses and provides metabolic support to axons. Differentiation of oligodendrocyte progenitor cells (OPCs) and Schwann cell (SC) precursors is critical for myelination during development and for myelin repair in demyelinating disorders. Myelination is tightly controlled by neuron-glia communication and requires the participation of a wide repertoire of signals, including neurotransmitters such as glutamate, ATP, adenosine or GABA. GABA is the main inhibitory neurotransmitter in the central nervous system (CNS) and it is also present in the peripheral nervous system (PNS). The composition and function of GABA receptors (GABARs) are well studied in neurons, while their nature and role in glial cells are still incipient. Recent studies demonstrate that GABA-mediated signaling mechanisms play relevant roles in OPC and SC precursor development and function, and stand out the implication of GABARs in oligodendrocyte (OL) and SC maturation and myelination. In this review, we highlight the evidence supporting that novel role of GABA with an emphasis on the molecular identity of the receptors expressed in these glial cells and the possible signaling pathways involved in their actions. GABAergic signaling in myelinating cells may have potential implications for developing novel reparative therapies in demyelinating diseases.